2023
DOI: 10.1002/ange.202218842
|View full text |Cite
|
Sign up to set email alerts
|

A Zeolite‐Like Metal–Organic Framework Based Membrane for Reverse Selective Hydrogen Separation and Butane Isomer Sieving

Abstract: Here, the fabrication of a defect-free membrane that is based on a zeolite-like metal-organic framework (ZMOF) with the underlying ana topology is reported. The unique ana-ZMOF structure provides high degree of pore connectivity, which is reflected by the fast transport of gases. Prominently, it offers an optimum pore-aperture size, affording notable sieving selectivity for butane/isobutane, and optimal pore energetics for reverse CO 2 /H 2 separation. This emphasize the potential for the application of pure M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…MOFs are porous inorganic materials that have received much attention recently owing to their outstanding characteristics, such as significant surface area and porosity, thermal/chemical stability, and tunability. MOFs are considered promising materials for a variety of potential applications across various fields, including gas storage and separation, chemical sensing, biomedical applications, adsorption, and heterogeneous catalysis. They are considered as one of the most promising physical adsorbent materials in the process of separating CO 2 /CH 4 . The engineering design of MOFs for gas separation applications is currently a rapidly growing area of research. Numerous experimental and simulation-based studies have been documented involving the separation of CO 2 from CH 4 through the use of MOFs. Considering the quadrupole moment and polarizability of CO 2 , current research efforts to enhance CO 2 uptake and selectivity primarily involves strategies aimed at improving the interaction between CO 2 and the frameworks. These include, but are not limited to, the utilization of various open metal sites, the insertion of functional groups, , the development of smart adsorbents, and ligand shortening in MOFs. , An investigation showed that MOF-801­(Ce) displayed improved separation performance for CO 2 /N 2 and CO 2 /CH 4 compared to MOF-801­(Zr/Hf) .…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are porous inorganic materials that have received much attention recently owing to their outstanding characteristics, such as significant surface area and porosity, thermal/chemical stability, and tunability. MOFs are considered promising materials for a variety of potential applications across various fields, including gas storage and separation, chemical sensing, biomedical applications, adsorption, and heterogeneous catalysis. They are considered as one of the most promising physical adsorbent materials in the process of separating CO 2 /CH 4 . The engineering design of MOFs for gas separation applications is currently a rapidly growing area of research. Numerous experimental and simulation-based studies have been documented involving the separation of CO 2 from CH 4 through the use of MOFs. Considering the quadrupole moment and polarizability of CO 2 , current research efforts to enhance CO 2 uptake and selectivity primarily involves strategies aimed at improving the interaction between CO 2 and the frameworks. These include, but are not limited to, the utilization of various open metal sites, the insertion of functional groups, , the development of smart adsorbents, and ligand shortening in MOFs. , An investigation showed that MOF-801­(Ce) displayed improved separation performance for CO 2 /N 2 and CO 2 /CH 4 compared to MOF-801­(Zr/Hf) .…”
Section: Introductionmentioning
confidence: 99%